Ecuador, microcrédito: ¿Negocio o inclusión financiera? - Salinas Vásquez, Juanita (2011)
A matched difference between the effective rate that banks and other not government institutions that work with microcredit charge and the effective rate charged by some saving and credit cooperative is presented here. Four basic criterions argument the situation: the possibility of reaching scale economies, high performance, the handle of operational costs and finally the need of credit risk protection.